Dilatar limites : a “ideia geral” de Luís de Albuquerque (1772-1781) - Moraes, Benone da Silva Lopes (2011)
This dissertation analyzes the set of documents, consisting of maps and texts, called Ideia Geral, made in 1780-81 by Luís de Albuquerque de Melo Pereira e Cáceres, governor of the capitania of Mato Grosso at the time. The goal is to understand its construction, linking the text and the map information, taking the period between 1772 and 1781 as timelines. Thus, a study of cartographic science of the eighteenth century was under taken as well, for it was through its use that the occupation of the South America’s inland, by the Iberian crowns found logistical support. This happened mainly in the context of the Treaties of Limits, as the Madrid (1750) and the Santo Ildefonso (1777) treaties. However, the dividing line proposed in both agreements left the area that had been occupied by the Lusitanian exposed in the western border, since the creation of the capitania of Mato Grosso (1748). To solve this issue and ensure the conquered territory, after signing the agreement of 1777, Luis de Albuquerque made the proposal to fix the boundary line in order to preserve the Lusitanian occupied territories. Entering the Ideia Geral leads us to think about the importance of the Mato Grosso limits in the construction of Brazil’s borders, since it presents a contemporary vision of the period of territorial disputes in South America undertaken by the Iberian kingdoms.